2009
DOI: 10.1177/0363546508328107
|View full text |Cite
|
Sign up to set email alerts
|

Video Analysis of Anterior Cruciate Ligament Injury

Abstract: Initial ground contact flatfooted or with the hindfoot, knee abduction and increased hip flexion may be risk factors for anterior cruciate ligament injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
388
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(419 citation statements)
references
References 27 publications
(54 reference statements)
16
388
2
5
Order By: Relevance
“…There is a significant amount of earlier international research that prove the high ratio of injuries in football (30,31,37,48) and the fact that these injuries most frequently occur in the lower extremities (20,21), where the largest single risk factor for the footballers consists of the non-contact injury of the anterior cruciate ligament (ACL) (1,22,59). Furthermore, the quality of movement patterns, especially the lower extremity patterns, is an important and modifiable factor that may influence the risk of ACL injury as well as play a critical role in injury mechanism (2,6,14). In order to reduce the frequency of these injuries, advice regarding prevention and rehabilitation is needed with actual strengthening programs for the treatment of the muscle imbalance, stretching exercises to moderate muscle stiffness, as well as proprioceptive programs for the improvement of balance and bodily movement (4,27,47).…”
mentioning
confidence: 99%
“…There is a significant amount of earlier international research that prove the high ratio of injuries in football (30,31,37,48) and the fact that these injuries most frequently occur in the lower extremities (20,21), where the largest single risk factor for the footballers consists of the non-contact injury of the anterior cruciate ligament (ACL) (1,22,59). Furthermore, the quality of movement patterns, especially the lower extremity patterns, is an important and modifiable factor that may influence the risk of ACL injury as well as play a critical role in injury mechanism (2,6,14). In order to reduce the frequency of these injuries, advice regarding prevention and rehabilitation is needed with actual strengthening programs for the treatment of the muscle imbalance, stretching exercises to moderate muscle stiffness, as well as proprioceptive programs for the improvement of balance and bodily movement (4,27,47).…”
mentioning
confidence: 99%
“…Theories have proposed various contributors to or risk factors for injury: intrinsic [1][2][3][4] and extrinsic 1,[4][5][6] entities; the antagonist-agonist relationships 7,8 ; quadriceps contraction 4 ; and, more recently, axial compressive forces on the lateral aspect of the joint [9][10][11][12] . Initial reports on mechanisms of anterior cruciate ligament injury were based on interviews with the athletes or descriptive analyses of videotapes 1,5,13 .…”
mentioning
confidence: 99%
“…Initial reports on mechanisms of anterior cruciate ligament injury were based on interviews with the athletes or descriptive analyses of videotapes 1,5,13 . A recent study of the one-limb landing positions associated with anterior cruciate ligament injury and noninjury found that injury occurred when the foot was less plantar flexed and the hip was more flexed during landing 11 . On the basis of these findings, socalled safe and provocative landing positions were defined and the average hip, knee, and ankle angles at initial ground contact were determined from videotapes of athletes during noncontact one-limb landings.…”
mentioning
confidence: 99%
“…Most biomechanical studies on anterior cruciate ligament injury are limited to data and research performed in laboratory (12). Video analysis and radiography yield better information about biomechanical and biological relation between hip, knee, ankle and their related pathology (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Most biomechanical studies on anterior cruciate ligament injury are limited to data and research performed in laboratory (12). Video analysis and radiography yield better information about biomechanical and biological relation between hip, knee, ankle and their related pathology (12)(13)(14). Future research strategies are aimed to find a simple method to find risk factors of anterior cruciate ligament injury to provide better prevention programs to decrease serious injury, but main factors playing a role in this event are still debatable (6, 7).…”
Section: Introductionmentioning
confidence: 99%